Assessment of the efficacy of an attenuated live marker classical swine fever vaccine (Flc-LOM-BErns) in pregnant sows - Lim, Seong-in; Choe, SeEun; Kim, Ki-Sun; Jeoung, Hye-Young; Cha, Ra Mi; Park, Gil-Soon; Shin, Jihye; Park, Gyu-Nam; Cho, In-Soo; Song, Jae-Young; Hyun, Bang-Hun; Park, Bong-Kyun; et al. (Vaccine, 2019)
•The Flc-LOM-BErns is live attenuated DIVA vaccine for CSFV.•The Flc-LOM-BErns vaccine protected foetuses from vertical transmission.•The Flc-LOM-BErns vaccine enables differential identification of serum antibodies. Here, we constructed an attenuated live marker classical swine fever (CSF) vaccine (Flc-LOM-BErns) to eradicate CSF. This was done by taking infectious clone Flc-LOM, which is based on an attenuated live CSF vaccine virus (LOM strain), and removing the full-length classical swine fever virus (CSFV) Erns sequences and the 3′ end (52 base pairs) of the CSFV capsid. These regions were substituted with the full-length bovine viral diarrhoea virus (BVDV) Erns gene sequence and the 3′ end (52 base pairs) of the BVDV capsid gene. Sows were vaccinated with the Flc-LOM-BErns vaccine 3 weeks before insemination and then challenged with virulent CSFV at the early, mid- or late stages of pregnancy. We then examined transplacental transmission to the foetuses. Piglets born to sows vaccinated with Flc-LOM-BErns did not show vertical infection, regardless of challenge time. In addition, CSFV challenge did not affect the delivery date, weight or length of the foetus. Pregnant sows inoculated with the Flc-LOM-BErns vaccine were anti-CSF Erns antibody-negative and anti-BVDV Erns antibody-positive. Challenge of pregnant sows with virulent CSFV resulted in anti-CSF Erns antibody positivity. These results strongly indicate that differential diagnosis can be conducted between the Flc-LOM-BErns vaccinated animal and virulent CSFV affected animal by detecting antibody against BVDV Erns or CSF Erns gene. Therefore, the Flc-LOM-BErns vaccine may fulfil the function of differential diagnosis which required for DIVA vaccine.